2005
DOI: 10.1111/j.1747-4477.2005.tb00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing The Quality Of Anaesthesia In Normal And Inflamed Teeth By Pulp Testing

Abstract: Failure to achieve complete anaesthesia of teeth with acutely inflamed pulps is a well-known clinical symptom. In this study, we compared the quality of anaesthesia in intact and inflamed mandibular teeth by using an electric pulp tester. Thirty patients with inflamed lower teeth, which had spontaneous or night pain, were selected; two healthy teeth in the same quadrant were used as control teeth. Electric pulp testing and thermal tests were made on each inflamed and control tooth. Teeth were then anaesthetise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
0
10
0
4
Order By: Relevance
“…The failure rate for inferior alveolar nerve block in clinical endodontic studies in patients with irreversible pulpitis is 44%-81% (1). The phenomenon of anesthetic resistance of inflamed dental pulps is well-documented in several studies (1)(2)(3)(4)(5). This phenomenon might have peripheral or central sources.…”
mentioning
confidence: 98%
“…The failure rate for inferior alveolar nerve block in clinical endodontic studies in patients with irreversible pulpitis is 44%-81% (1). The phenomenon of anesthetic resistance of inflamed dental pulps is well-documented in several studies (1)(2)(3)(4)(5). This phenomenon might have peripheral or central sources.…”
mentioning
confidence: 98%
“…The first explanation might relate to pathological changes within the pulp chamber. Failure to obtain complete anaesthesia of patients with acute pulpitis is well known and has been documented in several studies. It was reported that 57% to 89% of patients presenting with irreversible pulpitis have the potential for moderate to severe pain even with a nerve block.…”
Section: Discussionmentioning
confidence: 99%
“…Cold stimulation targeted unmyelinated C sensory nerve fibers, and EPT targeted myelinated A delta sensory nerve fibers. [10][11][12][13] Assessment of pain level during the injection was reported by each participant using a 10-point Likerttype scale anchored by ''no pain'' and ''worst pain imaginable.'' A timed assessment was performed for clinical onset of anesthesia by the participant reporting the time after injection to a numb midface.…”
Section: Data Collectionmentioning
confidence: 99%